Nickel ion release of niti archwire in variations of immersion time and toothpaste - Syamsiar Cahayati; Lusiana Batubara; Diah Ajeng Purbaningrum; Budi Wibowo (Majalah Kedokteran Gigi Indonesia, 2022)
Nickel-titanium archwires in orthodontic wires have nickel ion releases. The use toothpaste and saliva immersion time may cause its releases. This study aims to prove the difference and interaction between immersion time and toothpaste variations towards the amount of nickel ion releases at nickel-titanium archwires. The study was an experimental research with a post-test only control group design. Twenty seven nickel-titanium archwires were divided into three groups, i.e., K group, which were immersed in artificial saliva. P1 was immersed in artificial saliva and 1.5 gram of toothpaste A, and P2 was immersed in artificial saliva, and 1.5 gram of toothpaste B. The samples were incubated (37 °C) for 1 and 1.5 months. Nickel ion released was analyzed using SSA. Two Way ANOVA and Post Hoc LSD test were the statistic test used. The results of this study were the K group which released 0.112 mg/l and 0.685 mg/l, P1 which released 0.093 mg/l and 0.670 mg/l, and P2 which released 0.099 mg/l and 0.657 mg/l. There were differences in toothpaste variations (p = 0.029), differences in immersion time (p = 0.000) and there was no interaction between immersion time and toothpaste variations (p = 0.505) on the amount of nickel ion release. There was a significant difference in K-P1 (p = 0.038), K-P2 (p = 0.013), P1-P2 (p = 0.049). There was a difference in immersion time and toothpaste variation, but there was no interaction between immersion time and toothpaste variation towards the amount of nickel ion releases.